STRATEGI PENGEMBANGAN SWOT AGROWISATA DI DESA PANDANSARI LOR, KABUPATEN MALANG - Hesti Triana Soelistyari; Rizki Alfian; Debora Budiyono (Universitas Tribhuwana Tunggadewi, 2020)
Most of Indonesia's area is rural with various potentials and production resources. The dominant rural characteristics in Indonesia are agriculture resources based, as land resources, cultivation, processing, post-harvest, marketing, and tourism. The tourism sector has synergistic strength and is closely linked with various other development sectors. Pandansari Lor Village is one of the villages in Jabung District, Malang Regency, where most of the land used as agricultural land which has the potential to be developed into an agro-tourism village. The research objectives are to find out how the agrotourism development strategy in Pandansari Lor Village, Jabung District and make recommendations for agrotourism development in Pandansari Lor Village. Based on the SWOT analysis, the most important development strategy is to optimize existing agrotourism activities and other supporting agrotourism objects/attractions.